(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The analysis of lexical - semantical group of verbs of uncontrolled action is carried out in modern Ukrainian in the article; it is defined its semantic signs; paradigm and syntagmatical properties of verbs are described with sema «uncontrolled».